The influence of visual perspective on the somatosensory steady-state response during pain observation - Canizales, Dora L.; Voisin, Julien I.; Michon, Pierre-Emmanuel; Roy, Marc-André; Jackson, Philip L. (Frontiers in Human Neuroscience, 2013)
The observation and evaluation of other's pain activate part of the neuronal network involved in the actual experience of pain, including those regions subserving the sensori-discriminative dimension of pain. This was largely interpreted as evidence showing that part of the painful experience can be shared vicariously. Here, we investigated the effect of the visual perspective from which other people’s pain is seen on the cortical response to continuous 25 Hz non-painful somatosensory stimulation (somatosensory steady-state response: SSSR). Based on the shared representation framework, we expected first-person visual perspective (1PP) to yield more changes in cortical activity than third-person visual perspective (3PP) during pain observation. Twenty healthy adults were instructed to rate a series of pseudo-dynamic pictures depicting hands in either painful or non-painful scenarios, presented either in 1PP (0°-45° angle) or 3PP (180° angle), while changes in brain activity was measured with a 128-electode EEG system. The ratings demonstrated that the same scenarios were rated on average as more painful when observed from the 1PP than from the 3PP. As expected from previous works, the SSSR response was decreased after stimulus onset over the left caudal part of the parieto-central cortex, contralateral to the stimulation side. Moreover, the difference between the SSSR was of greater amplitude when the painful situations were presented from the 1PP compared to the 3PP. Together, these results suggest that a visuospatial congruence between the viewer and the observed scenarios is associated with both a higher subjective evaluation of pain and an increased modulation in the somatosensory representation of observed pain. These findings are discussed with regards to the potential role of visual perspective in pain communication and empathy.